THE LEGAL FRAMEWORK FOR THE CRIME OF SEXUAL HARASSMENT: AN APPLIED STUDY IN THE JORDANIAN JUDICIARY (Journal of Namibian Studies : History Politics Culture, 2023)
Any country's duty to protect women and men begins with protecting the body from sexual assault, which has been criminalised by the Jordanian Penal Code through explicit provisions criminalising a number of crimes, such as rape when the victim is female only, molestation when the victim is male or female, or inappropriate flirtation in public or in private. The Jordanian Penal Code did not address verbal or gesture sexual harassment. Would traditional provisions criminalise the same or need explicit legal measures be made? In addition, what is the criterion for the existence or non-existence of sexual harassment, which has been spreading largely in the Jordanian community? Sexual harassment is mostly represented by sexual expressions that encroach on the dignity of the female or male, but the victim is mostly a female, half of the community, who suffers psychological and physical damage from this crime. We reached several results and recommendations that the Jordanian Penal Code does not specifically state about sexual harassment, but the laws of criminalization may be a reference. In actuality, sexual harassment is broader than the Jordanian Penal Code, including simple catcalls, inappropriate comments, and minor events that are judged by the person and their psychological impact. I urge adding article 306 et al. to the Jordanian Penal Code to specifically criminalise sexual harassment.